The Effects of the Type and Amount of Information in Sex Discrimination Research: A Meta-Analysis - Tosi, Henry L.; Einbender, Steven W. (Academy of Management Journal, 1985)
For the past several years and for obvious reasons, there has been much research about discrimination in workplaces. These studies, which examine the relationship of factors such as gender, race, age, and handicaps to personnel decisions, are essentially designed to test whether or not there is bias in hiring, promotion, or other equally important career or work decisions. These studies have rather similar designs: subjects taking the role of a personnel decision maker are asked to decide which applicant from a group of men and women is most suited for a job. To present stimuli, experimenters use resumes, in-basket problems, sometimes videotapes, and, rarely, a field setting. This body of research has not been particularly helpful in resolving the question of discrimination in selection, as the studies are almost evenly divided?about half show that discrimination occurs and half show otherwise. After an extensive review of this research, Arvey (1979) suggested that, in general, women are evaluated more poorly than men, except when evaluators have information about qualifications of candidates. Then, the competence of candidates plays a major role in assessment. This suggests that differences in the results of these studies could be a function of the amount and type of information that individuals have for deciding between men and women applicants. When judges have limited information, they are more likely to base a decision on sex-role stereotypes, favoring men over women for jobs that men have traditionally done, but when applicant information is not so limited, there is little need to rely on stereotypes (Renwick & Tosi, 1978). If this is so, the logical argument that follows is that those studies showing discrimination provided judges with less information and more gender-salient cues than those studies that showed no discrimination. This paper tests the proposition that raters faced with more job-relevant information about an applicant and a job will make less biased decisions than raters faced with less job-relevant information. After reviewing the research on unfair discrimination, Arvey raised the following question: ?Does the amount of information about candidates and jobs affect differential evaluation?? (1979: 761). The following analysis indicates that the answer is yes.